Treatment monitoring and mortality risk adjustment in anaemic Jehovah's Witnesses. (17th September 2012) - Beliaev, Andrei M.; Marshall, Roger J.; Smith, Warren; Windsor, John A.
Abstract Background Management of anaemic Jehovah's Witness (JW) patients, who refuse blood transfusion on religious grounds, is challenging. In the published literature, there are few cohort studies that consider causes of mortality in isolation and are lacking in their predictive power. This does not allow clinicians to monitor treatment progress of severely anaemic JW patients and adjust their risk of mortality. The study aims to develop an anaemia‐related mortality risk prediction instrument. Methods This retrospective cohort study evaluated anaemia‐related mortality risk factors of JW patients. JW patients were identified from the records of four major public hospitals in the Auckland and Midlands regions of New Zealand (North Shore, Auckland City, Middlemore and Waikato hospitals) for the period 1998 to 2007 inclusive. The inclusion criteria were age ≥15 years and severe anaemia (haemoglobin concentration ≤80 g/L). Palliative care cancer patients were excluded. Results Anaemia‐related risk factors of mortality for JW patients were identified, weighted and used to construct a mortality risk predictive score (the Hamilton Anaemia Mortality Risk Score (Hamilton AMRS)). This permitted stratification of JW patients into mortality risk groups according to their Hamilton AMRS. It is shown that patients with Hamilton AMRS of 0 to 2 had 4% mortality, patients with Hamilton AMRS of 3 to 4 had 29% mortality, patients with Hamilton AMRS of 5 had 40% mortality and patients with Hamilton AMRS of ≥6 had 67% mortality. Conclusion The Hamilton AMRS allows treatment monitoring of anaemic JW patients and adjustment of their risk of mortality.